Business ethics ( A Stakeholder and Issues Management Approach) - Weiss, Joseph W. (2015)
The sixth edition of Business Ethics: A Stakeholder and Issues Management Approach continues the mission of providing a practical, easy- to- read, engaging and contemporary text with detailed real- time contemporary and classic cases for students. This text updates the previous edition, adding fourteen new cases in addition to other new features discussed below. We continue our quest to assist colleagues and students in understanding the changing environment from combined stakeholder and issues management approaches, based on the theory and practice that fi rms depend on stakeholders as well as stockholders for their survival and success. Acting morally while doing business is no longer a joking or even questionable topic of discussion. With the near shutdowns of the U.S. government, the subprime lending crisis, global climate changes, the fading middle class in America and other countries, China’s continuing economic expansion, and India’s inroads into the global economy, the stakes for the global economy are not trivial. Ethical behaviors are required, not optional, for this and future generations. Learning to think and reason ethically is the fi rst step...